Environmental benefits from shared-fleet logistics: lessons from a public-private sector collaboration. Issue 2 (1st February 2023) - Grote, Matt; Cherrett, Tom; Whittle, Gary; Tuck, Neil
ABSTRACT: Road freight transportation leads to environmental concerns such as congestion and detrimental vehicle emissions, whilst also suffering from inefficiencies due to less-than-full-load vehicle movements. Shared-fleet carrier collaborations are an approach to freight distribution that can reduce inefficiencies, and thereby reduce goods vehicle-kilometres (vkm) and associated congestion and emissions. Using real-world data from a five-day warehouse survey, the potential environmental benefits of a shared-fleet operation involving collaboration between local suppliers to a large commercial enterprise and a municipal Local Government Authority (LGA) were quantified. Local suppliers shared the spare capacity in LGA courier service vans (Light Goods Vehicles) to transport consignments as an alternative to each organising their own separate deliveries. Results suggested a shared-fleet carrier collaboration involving 25 local suppliers serviced by five LGA vans performing 16 rounds/week produced a 29% reduction in delivery vkm and emissions reductions ranging from 27-36% depending on pollutant.